Increased risk of non-alcoholic fatty liver disease fibrosis is closely associated with osteoporosis in women but not in men with type 2 diabetes. Issue 11 (12th October 2022) - Yu, Zhiyan; Wu, Yueyue; Zhang, Rui; Li, Yue; Zang, Shufei; Liu, Jun
Abstract : Background: This study aimed to investigate the association of non-alcoholic fatty liver disease (NAFLD) and liver fibrosis with osteoporosis in postmenopausal women and men over 50 years of age with type 2 diabetes (T2DM). Methods: In this study, 1243 patients with T2DM (T2DM with coexistent NAFLD, n = 760; T2DM with no NAFLD, n = 483) were analysed. Non-invasive markers, NAFLD fibrosis score (NFS) and fibrosis index based on four factors (FIB-4), were applied to evaluate NAFLD fibrosis risk. Results: There was no significant difference in bone mineral density (BMD) between the NAFLD group and the non-NAFLD group or between males and females after adjusting for age, BMI and gender. In postmenopausal women, there was an increased risk of osteoporosis (odds ratio (OR): 4.41, 95% CI: 1.04–18.70, P = 0.039) in the FIB-4 high risk group compared to the low risk group. Similarly, in women with high risk NFS, there was an increased risk of osteoporosis (OR: 5.98, 95% CI: 1.40–25.60, P = 0.043) compared to the low risk group. Among men over 50 years old, there was no significant difference in bone mineral density between the NAFLD group and the non-NAFLD group and no significant difference between bone mineral density and incidence of osteopenia or osteoporosis among those with different NAFLD fibrosis risk. Conclusion: There was a significant association of high risk for NAFLD liver fibrosis with osteoporosis in postmenopausal diabetic women but not men. In clinical practice, gender-specific evaluation of osteoporosis is needed in patients with T2DM and coexistent NAFLD.